2018
DOI: 10.1002/brb3.1205
|View full text |Cite
|
Sign up to set email alerts
|

Resting‐state connectivity within and across neural circuits in anorexia nervosa

Abstract: Introduction Obsessional thoughts and ritualized eating behaviors are characteristic of Anorexia Nervosa (AN), leading to the common suggestion that the illness shares neurobiology with obsessive–compulsive disorder (OCD). Resting‐state functional connectivity MRI (rs‐fcMRI) is a measure of functional neural architecture. This longitudinal study examined functional connectivity in AN within the limbic cortico‐striato‐thalamo‐cortical (CSTC) loop, as well as in the salience network, the default mode network, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 91 publications
3
19
2
Order By: Relevance
“…Differences to previous research indicating persistent alterations in varying brain networks in short- (Uniacke et al, 2019) and long-term recovered AN (Boehm et al, 2016;Cowdrey et al, 2014;Favaro et al, 2012;Scaife et al, 2017) may be due to the longer average recovery time (5.3 ± 3 years) and the considerably shorter illness durations in our cohorts (tables S20, S21). This further underlines the importance of early identification and treatment of AN during adolescent age (Zipfel et al, 2015).…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Differences to previous research indicating persistent alterations in varying brain networks in short- (Uniacke et al, 2019) and long-term recovered AN (Boehm et al, 2016;Cowdrey et al, 2014;Favaro et al, 2012;Scaife et al, 2017) may be due to the longer average recovery time (5.3 ± 3 years) and the considerably shorter illness durations in our cohorts (tables S20, S21). This further underlines the importance of early identification and treatment of AN during adolescent age (Zipfel et al, 2015).…”
Section: Discussioncontrasting
confidence: 98%
“…In line with several previous publications, we find largely decreased intra-and interregional rsfMRI measures in acute AN in bilateral prefrontal, sensorimotor, left parietal, left temporal, bilateral precuneal and insular regions (Ehrlich et al, 2015;Favaro et al, 2012;Gaudio et al, 2015Gaudio et al, , 2018Geisler et al, 2016;Haynos et al, 2019;Kullmann et al, 2014;Phillipou et al, 2016;Scaife et al, 2017;Seidel et al, 2019). In contrast to some previous studies, we do not find increases of intraregional (Seidel et al, 2019) or interregional FC and activity (Biezonski et al, 2016;Boehm et al, 2014;Cha et al, 2016;Lee et al, 2014;Uniacke et al, 2019). This discrepancy may be due to differences in sample size, methodology as well as in most cases' shorter illness duration and younger age of our sample (table S19).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The longitudinal changes in DMN activation observed here during performance of a DD task dovetail with previous findings of alterations in these regions in individuals with AN, both at rest [66,67] and during other self-relevant decision-making tasks [69][70][71][72]. Although supplementary analyses of functional connectivity between the identified DMN regions and task-positive FPN regions did not detect significant longitudinal differences, future-focused analysis of antagonism between task-positive and task-negative networks [83] might provide a unique window on brain function and dysfunction in AN [84][85][86]. Second, our findings also provide further evidence underlining the volatility of DD [78] and suggest that alterations in AN likely do not constitute a trait of the disorder, as might be inferred from recent meta-analytic data [19,24].…”
Section: Discussionsupporting
confidence: 71%
“…26 Some studies have demonstrated aberrant functional within-and between-network connectivity of the salience network in anorexia nervosa, but others found only indirect evidence for salience network abnormalities in patients in the acutely underweight state. 27,28 Importantly, studies in healthy participants have observed that activity in key nodes of the salience network -including the amygdala 29 and insula, 30 as well as amygdala connectivity 31 -might depend on SLC6A4 methylation. Using a monozygotic twin design, a recent study demonstrated an association between SLC6A4 methylation and brain responses to negative stimuli in frontal-limbic regions overlapping the salience network that was independent of DNA sequence variations.…”
Section: Introductionmentioning
confidence: 99%